Interação entre osmorreceptores e mecanismos colinérgicos e angiotensinérgicos prosencefálicos no controle da ingestão de sódio - Roncari, Camila Ferreira (2014)
Sodium intake is induced by facilitatory signals, such as angiotensin II (ANG II) and aldosterone. Hyperosmolarity and central cholinergic activation, classic antinatriorexigenic stimuli, also induce NaCl intake when the inhibitory mechanisms of the lateral parabrachial nucleus (LPBN) are deactivated. In the present study, we investigated the possible interaction between osmoreceptors and cholinergic and angiotensinergic mechanisms in the control of water and NaCl intake induced by different dipsogenic and/or natriorexigenic stimuli combined with the blockade of LPBN inhibitory mechanisms. Rats with stainless steel cannulas implanted in the lateral ventricle (LV) or subfornical organ (SFO) and bilaterally into the LPBN were used to study the effects of injections of atropine (muscarinic cholinergic antagonist), losartan or ZD 7155 (AT1 receptor antagonists) into the LV or SFO on water and 0.3 M NaCl intake induced by bilateral injections of moxonidine (α2- adrenoceptor/imidazoline agonist) into the LPBN combined with a) plasma hyperosmolarity induced by intragastric (ig) 2 M NaCl; b) injections of carbachol (cholinergic agonist) into the LV or SFO; c) subcutaneous injections of furosemide (FURO) and captopril (CAP); d) injection of ANG II into the LV. Additionally, we also investigated whether acute application of osmotic, angiotensinergic and cholinergic stimuli would activate cultured SFO dissociated cells and if the same cell would be activated by different stimuli. In rats treated with ig 2 M NaCl, injections of moxonidine (0.5 nmol/0.2 μl) into the LPBN increased water and 0.3 M NaCl intake. Injections into the LV or SFO of atropine (20 nmol/1.0 μl and 2 nmol/0.1 μl, respectively) or losartan (100 μg/1.0 μl and 1 μg/0.1 μl, respectively) abolished water and 0.3 M NaCl intake in rats treated with ig 2 M NaCl combined with moxonidine into the LPBN. Moxonidine injected into the LPBN also increased water and 0.3 M NaCl intake induced by FURO + CAP, injections of ANG II (50 ng/1.0 μl) and carbachol (4 nmol/1.0 μl) into the LV or carbachol (0.5 nmol/0.1 μl) into the SFO. The blockade of AT1 receptors with injections of losartan into the LV or ZD 7155 (1 μg/0.1 μl) into the SFO abolished water and 0.3 M NaCl intake in rats treated with carbachol into the LV or SFO combined with LPBN injections of moxonidine. However, atropine injected into the LV, despite reducing water intake, did not change 0.3 M NaCl intake in rats treated with FURO + CAP or injection of ANG II into the LV combined with injections of moxonidine into the LPBN. Injections of losartan into the LV reduced 0.06 M sucrose intake, but did not change food intake induced by 24 h of food deprivation. Finally, in vitro studies showed that osmotic, angiotensinergic and cholinergic stimuli activate SFO dissociated cells and that different stimuli can activate the same SFO cell. Therefore, the results of the present study suggest that different stimuli, such as hyperosmolarity and central cholinergic activation, facilitate NaCl intake through activation of central angiotensinergic mechanisms.